The impact of metal leaching in MOF materials on the evaluation of photocatalytic CO2 reduction activity – A case study - Zhengqiu Wu; Yunliang Yu; Jia Chen; Yuliang Liu; Chao Zou (Next Energy)
Most photocatalyzed CO2 reduction systems employed visible light photosensitizer, metal-containing CO2 reduction catalyst and sacrificial reagent, demonstrating excellent efficiency and high selectivity. However, the influence of metal ion leached from decomposition of trace amounts of metal-containing catalyst has rarely been discussed. Here, we discovered that leaching Fe ion from Fe-MOF during the catalyzed CO2 reduction process was the crucial species for efficient CO2 reduction in our system which utilized [Ru(bpy)3]Cl2·6H2O as photosensitizer, tri-isopropanolamine (TIPA) as sacrificial reagent and Fe-MOF as CO2 reduction catalyst. FeCl3 was tested as CO2 reduction catalyst instead of Fe-MOF and provided 73,750 μmol g−1 h−1 of CO in MeCN, 329,500 μmol g−1 h−1 in N,N-Dimethylformamide after 4 h of visible light irradiation. Additionally, we investigated other metal chlorides (Na, Cr, Mn, Ni et, al.) to study the effect of Fe ion. Both Fe3+, Co2+ and Ni2+ provided satisfactory catalytic efficiency which indicated that the effect of metal ion leaching in Metal-organic frameworks (MOFs) contained photocatalytic CO2 reduction systems should be appreciated. Furthermore, the concentration of Cl− also played a beneficial role and enhanced the catalysis process.